Technology transfer and training / Iza Syahida Yusof - Yusof, Iza Syahida (Faculty of Information Management, 2002)
This study highlights the new development of technology transfer and training. The researcher employs the new method about the effective training to make a smooth transfer of technology by one place to another place. It begins with studies out the definition of all phrases that related to technology transfer. The actual objective of this study is to see the best type implementation of training in technology transfer. Because the successful route of technology transfers development is training. Training is needed to lessen the hazards that will loom ahead and create a high skill of manpower. So in this study will cover what are technology transfer training, and the process working. Also include the descried of phrase technology, training, and technology transfer itself. Overall this study is to future improvement in transferred the technology and training.